Organic matter loading by hippopotami causes subsidy overload resulting in downstream hypoxia and fish kills - Dutton, Christopher L.; Subalusky, Amanda L.; Hamilton, Stephen K.; Rosi, Emma J.; Post, David M. (Nature communications, 2018)
Organic matter and nutrient loading into aquatic ecosystems affects ecosystem structure and function and can result in eutrophication and hypoxia. Hypoxia is often attributed to anthropogenic pollution and is not common in unpolluted rivers. Here we show that organic matter loading from hippopotami causes the repeated occurrence of hypoxia in the Mara River, East Africa. We documented 49 high flow events over 3 years that caused dissolved oxygen decreases, including 13 events resulting in hypoxia, and 9 fish kills over 5 years. Evidence from experiments and modeling demonstrates a strong mechanistic link between the flushing of hippo pools and decreased dissolved oxygen in the river. This phenomenon may have been more widespread throughout Africa before hippopotamus populations were severely reduced. Frequent hypoxia may be a natural part of tropical river ecosystem function, particularly in rivers impacted by large wildlife. Hypoxic (low oxygen) water conditions are generally thought to be uncommon in rivers and result from human impacts. However, Dutton and colleagues show here that waste from hippos in the Mara River contributes to frequent hypoxic events, suggesting hypoxia is a natural aspect of this system.